论中国国有企业经营者的选任，激励和监督机制 = Managers of state-owned enterprises in China : selection, incentive and supervision mechanism - 杜金卿 Du, Jinqing (2008)
The reform of state-owned enterprises plays a center role in China's economic system reform. One of the key problems of state-owned enterprises in China is how to select, supervise and provide right incentives to their managers. The purpose of this paper is to find out a systematic method to solve the problem mentioned above. To do so, the paper analyses the managers' behavior of state-owned enterprises, based on the principal-agent theory and the survey of 60 managers of 20 enterprises in QingHuangDao City, P. R. China.